Reseña de la obra "Kant´s Doctrine of Right in the Twenty-first Century" - Vázquez Peñas, Aarón (Revista de Humanidades, 2020)
Reseña de / Book review of: Krasnoff, Larry; Sánchez Madrid, Nuria; Satne, Paula (eds.) (2018). Kant´s Doctrine of Right in the Twenty-first Century. Cardiff: University of Wales Press, 244 pp.